Synthesis of Nanoporous TiO2 and Its Potential Applicability for Dye-Sensitized Solar Cell Using Antocyanine Black Rice - Brian Yuliarto; Wilman Septina; Kasyful Fuadi; Fahiem Fanani; Lia Muliani; Nugraha (Advances in Materials Science and Engineering)
Nanoporous mesostructure TiO2 powders were synthesized by sol-gel method, with TiCl4 as a precursor in methanol solution. The Pluronic PE 6200 of block copolymer was used as the pores template. It was found from XRD measurements, both at 400∘C and 450∘C calcination temperatures, that the sol-gel technique yielded the nanoporous TiO2 with anatase phase. Based on N2 adsorption characterization using BET method, the TiO2 samples have surface area of 108 m2/g and 88 m2/g for calcination temperatures of 400∘C and of 450∘C, respectively. From small-angle neutron scattering (SANS) patterns, TiO2 samples were observed to have nanoporous structures with pore sizes between 22–24 nm. The TiO2 also have order degree which depends on the calcination temperature. The potential applicability of the resulting TiO2 is confirmed for dye-sensitized solar cell (DSSC), composed of nanoporous anatase TiO2 and natural dye from antocyanine black rice. UV-Vis measurement of dye extracted from the black rice indicated that the antocyanine chelate can propagate into the TiO2 nanoporous network. The short circuit photocurrent density (Jsc) under 100 mWcm−2 reached 1.287 mAcm−2 with open circuit photovoltage (Voc) of 550 mV and the fill factor of 33.4%. The results show that the hybrid organic-inorganic structures are very attractive for future low-cost devices.